Artificial Heart Valve Inspection Using Eddy Current Techniques - Tatiana Strapacova; Klara Capova; Ladislav Janousek (Communications - Scientific letters of the University of Zilina, 2011)
This paper discusses about minimally invasive techniques to detect the single leg fracture in special type of artificial heart valve called Bjork Shiley Convexo - Concave (BSCC). The fracture affects the outlet strut of these artificial heart valve and it is needed to detect it. For this purpose the electromagnetic methods based on eddy current testing were used. The coils are excited in the selected range of the frequencies for identification of the fractures in the outlet strut. The fractures occurring in BSCC heart valve and their numerical simulations are described. The results obtained with a prototype setup are presented and they demonstrate the usefulness of described techniques for detection of the outlet strut fractures in BSCC artificial heart valve.